Language Barriers: Language Training Mismatch and Communication Challenges among Indonesian Technical Intern (TITP) in Japan - Salombe', Fikarisma Daeng; Iskandar, Kurniawaty; Rustam, Muhammad Reza (KIRYOKU, 2025)
This study explores the language barriers faced by Indonesian low-skilled workers under the Technical Intern Training Program (TITP) in Japan. Data were collected through semi-structured interviews with four informants, each representing one of the following sectors: caregiving, fisheries, construction, and agriculture. The informants were selected using the snowball sampling technique. The findings reveal a linguistic mismatch between Japanese language training at LPKs (Job Training Institutions) in Indonesia and Accepting Organisations (AO) in Japan with the actual communication demands encountered in the workplace. While the training programs focus on grammar and standardized Japanese, they lack adequate preparation for the real-world, context-dependent communication skills needed in the workplace. Barriers such as limited understanding of technical terms and local dialects hinder effective adaptation. This study underscores the need for workplace-oriented, practical language training to enhance communication, productivity, and social integration of Indonesian TITP workers in Japan.